Geroderma osteodysplasticum: Histological features and the role of panel-based exome sequencing in diagnosis. (4th March 2018) - Jewell, Rosalyn; Brewer, Paul; Stenton, Sophie; Berry, Ian R; Chatfield, Sue; Fernandes, James A; Peres, Cesar; Wagner, Bart E; Bennett, Christopher
ABSTRACT: Geroderma osteodysplasticum (GO) has clinical and histological features that overlap with other causes of wrinkly skin. Here we present the case of a child diagnosed with GO following exome sequencing of a panel of genes covering the wide differential diagnosis. The histological features of the overlapping conditions are presented, highlighting the utility of panel testing for conditions of this type. This is relevant to many genetic conditions and can influence ongoing management as exemplified by this case.